Clinical and Histopathological Profile of Nasopharyngeal Carcinoma Patients in the Department of Otolaryngology-Head and Neck Surgery at Prof. Dr. I.G.N.G. Ngoerah General Hospital in 2022 – 2024 - Kadek Santi Diahswari Widyadari; Ni Putu Setiawathi; Ida Ayu Alit Widiantari (Green Publisher Indonesia, 2025)
Backgrounds: Nasopharyngeal carcinoma (NPC) is a form of carcinoma of the nasopharyngeal epithelium, where NPC is 6th as the most common carcinoma in Indonesia. This research aimed to find and get to know the clinical and histopathological profile of NPC patients in the Department of Otolaryngology-Head and Neck Surgery at Prof. Dr. I.G.N.G. Ngoerah General Hospital. Methods: This study is a descriptive observational study with a cross-sectional approach, conducted to determine the clinical and histopathological profile of NPC patients. Using total sampling method, data collection was carried out in May 2025 done by observing secondary data in the form of electronic medical records. The inclusion criteria of this study were patients diagnosed with NPC, patients could be from both male or female, patients of all ages, patients that have underwent examination for staging. Results: There were 186 NPC patients in this study. Patients diagnosed with NPC are more frequent in men (69,35%), in the age group of 45-54 years (37,63%), experiencing lump in the neck (68,82%), have histopathological features of undifferentiated cell carcinoma (98,92%), most patients were in the stage IVA (39,24%). Conclusion: NPC patients come with various sociodemographic backgrounds and different clinical conditions. This study found that NPC is more frequent in men than women, commonly diagnosed in the fourth and fifth decade of life, most patients experiencing lump in the neck. This study also found that the most common histopathological features were undifferentiated cell carcinoma. Most patients were in the stage IVA.